Detection of contagious caprine pleuropneumonia in East Turkey - Cetinkaya, B.; Kalin, R.; Karahan, M.; Atil, E.; Manso-Silvan, L.; Thiaucourt, F. (Office Int Epizooties, 2009)
A study was implemented to investigate the presence of contagious caprine pleuropneumonia (CCPP) in East Turkey. This study was based on clinical surveillance in the field, surveillance at regional slaughterhouses and regular submission of suspected lesions to regional laboratories. The results showed that the agent of CCPP, Mycoplasma capricolum subspecies capripneumoniae (Mccp), could be detected by culture and specific polymerase chain reaction from 37.5% (12/32) of lung samples taken from goats of ten different herds. This agent was also isolated from two of 13 sheep samples (one from the lung and the other from a nasal swab). Mycoplasma capricolum subsp. capripneumoniae was isolated in pure culture and characterised at a finer molecular level. The East Turkish isolate was found to be closely related to another strain of Turkish origin, as well as to Mccp strains isolated in Tunisia. The isolation of Mccp from sheep lung lesions brings the strict host-specificity of this pathogen into question. It may also indicate that Mccp presents a risk for wildlife in the region. Such results, the authors believe, demonstrate that adequate risk assessments should be undertaken in Turkey and neighbouring countries.
Keywords: Caprines; Contagious caprine pleuropneumonia; East Turkey; Goats; Isolation; Molecular characterisation; Mycoplasma capricolum subsp capripneumoniae; Mycoplasma mycoides cluster; Pleuropneumonia; Polymerase chain reaction; Sheep; Small ruminants; Turkey